Family satisfaction with involvement of family members in decision making in the intensive care unit: a scoping review - Baliki, Onalenna (My University, 2021)
Background: Critical care delivery for critically ill patients in the intensive care unit (ICU) has evolved away from patient centered care to a family centered care, where families are considered partners in the care of their loved one. Families of critically ill patients admitted in ICU remain the integral part of the healthcare system therefore family members as surrogate decision makers should be involved in the decisions making. Decision making in the intensive care unit is often complex, involving frequent interactions between patients, their families, and health care professionals regarding basic and advanced life-support technologies. Aim: The aim of the scoping review was to gather evidence related to family satisfaction with the involvement of family members in decision-making in the intensive care unit and to identify gaps and inconsistencies in the existing literature. Design: A scoping review guided by Arksey and O ‘Malley’s framework was carried out. This framework includes identifying the research question, identifying relevant studies, study selection, charting the data and reporting the results. Methods: A comprehensive literature search was conducted using CINAHL, Complete, Academic search and health science: nursing, MEDLINE, SCOPUS and PUBMED. All peer-reviewed studies published in English between 2010 and 2020 were retrieved. Results: A total of 149 articles were screened, of which 24 were eligible for analysis, including 17 quantitative, 6 qualitative and 1 mixed method studies. Four main themes emerged from the scoping reviewnamely: satisfaction, communication, involvement and support. Conclusion: There was a significant gap in research on the active participation of family membersin the clinical decision making process and factors influencing the family involvement in decision making.
A research report submitted to the Faculty of Health Sciences, University of the Witwatersrand, Johannesburg in partial fulfilmentof the requirements for the degree ofMaster of Science in Nursing, 2021